An exploratory study on Filipino millennial parents’ practice of sharenting - Crisologo, Naomi Faith T.; Sarmiento, Francheska Danielle R.; Jamero, Josephine Louise F. (Quezon City College of Home Economics, University of the Philippines Diliman, 2023)
Sharenting has become a prevalent practice in the past decade with changes in technology. However, there are few to no studies exploring the sharenting practices of Filipinos, despite being among the top users of social media. This study explores the sharenting practices of Filipino millennial parents (FMP), as well as the factors that lead to the practice, their decision-making process, and their overall experience with sharenting. Through purposive sampling, 10 FMP who actively post about their 0–5-year-old children and residing in Metro Manila were selected as the participants. The data was gathered using in-depth interviews and then analyzed thematically. Results show that FMP practice sharenting for memory-keeping, connecting with friends and family, and feeling a sense of community and belonging online. These were found to be internal or external factors affecting the parent's decision-making process. The factors then influence the decision-making process of FMP, with its steps similar to the sharenting practices of parents worldwide. Despite having concerns with the practice, results indicate that parents have a positive outlook on sharenting and will continue to practice it in the future as it serves their purpose. With this, sharenting primarily benefits FMP, even with the child’s interest in mind when practicing. The study's findings indicate the need for more in-depth exploration of the topic and other adjacent themes to better understand Filipino millennials' parenting practices and behavior and their implications on their children.
Thesis
Includes bibliographical references (pages 177-186)
Keywords: Parenting -- Social networks -- Philippines; Child rearing -- Philippines; Parents -- Philippines; Generation Y -- Philippines